Safe in her bodyguard's arms - Garbera, Katherine (Harlequin romantic suspense, 2024)
A drug cartel murdered Obie Keller's parents. She gets a chance to prove that when she leaves the Florida coast and heads back to where she came from--with bodyguard Xander Quentin by her side. His reasons for heading into the swamplands are intertwined with her own, and it's not long before their shared mission becomes a shared attraction. But they'll have to stay alive if they're going to have a shared future...